Two-dimensional black carbon nitride quantum material with room-temperature ferromagnetism as well as preparation method and application of two-dimensional black carbon nitride quantum material

The two-dimensional black carbon nitride material prepared by steps such as urea calcination and argon annealing solves the problems of complex preparation and environmental impact of existing two-dimensional carbon-based ferromagnetic materials, and realizes room temperature ferromagnetic properties with high purity and high magnetization strength Materials have promoted its application in the fields of spintronics and magnetic storage.

CN119430096AActive Publication Date: 2025-02-14XIDIAN UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411576723.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Due to the scarcity of raw materials, low Curie temperature, complex preparation process and natural biotoxicity, existing two-dimensional carbon-based ferromagnetic materials have high costs of research and application, large energy consumption, and burdens the environment, limiting their Practical use and commercialization process in the fields of spintronics, magnetic storage and topological quantum.

Method used

By using urea as raw material, calcined in the atmosphere, annealing and edge quadruple heat treatment in argon gas, introducing a large amount of nitrogen vacancy, a two-dimensional black carbon nitride quantum material with room temperature ferromagneticity was prepared. The process is simple, easy to repeat and low cost.

Benefits of technology

The prepared two-dimensional black carbon nitride material has high purity, high magnetization, high Curie temperature and strong room temperature ferromagneticity. It can be used in the fields of spintronic devices, topological quantum devices and magnetic storage, and promotes sp electron carbon The process of research and development of base room temperature ferromagnetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430096A_ABST
    Figure CN119430096A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional black carbon nitride quantum material with room-temperature ferromagnetism as well as a preparation method and application of the two-dimensional black carbon nitride quantum material. The carbon nitride quantum material is a two-dimensional layered amorphous nanosheet, and has a graphite-like phase structure with nitrogen vacancies in a carbon-nitrogen skeleton; the single-layer thickness of the carbon nitride quantum material is 4-15 nm, and the length or width of the carbon nitride quantum material is 1-10 [mu] m; the method comprises the following steps: calcining urea serving as a raw material in air, performing primary annealing and edge quadruple heat treatment, and performing centrifugal washing and low-temperature drying by using absolute ethyl alcohol to obtain the black carbon nitride quantum material, the preparation method disclosed by the invention has the characteristics of simple process, easiness in repetition and low cost; the black carbon nitride prepared by the preparation method disclosed by the invention has the characteristics of high purity, high magnetization intensity, high Curie temperature and strong room-temperature ferromagnetism, and can be applied to the fields of spinning electronic devices, topological quantum devices, magnetic storage and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum information materials, and specifically relates to a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, a preparation method and an application thereof. Background Art

[0002] Since the first experimental verification of two-dimensional ferromagnetic materials in 2017, many breakthroughs have been made in the fields of spintronics devices and topological quantum devices. Among them, two-dimensional ferromagnetic materials based on transition metals and rare earth elements have attracted much attention due to their rich magnetic ordered structures. However, due to the shortage of raw materials, low Curie temperature, complex preparation process and natural biological toxicity, these materials have high research and application costs, high energy consumption, and burden on the environment, which limits their practical use and commercialization in many fields. Carbon is a widely available and biocompatible lightweight element. Its rich bonding environment brings adjustable band gaps, making carbon-based materials as ferromagnetic semiconductors have great development advantages and non-negligible plasticity. Carbon-based ferromagnetic materials benefit from the spin provided by sp electrons, have a long spin lifetime and weak spin-orbit interaction, and are more easily resistant to the destructive effect of thermal disturbance on magnetic order in low dimensions, thereby achieving high-temperature ferromagnetism, but its weak magnetic strength hinders further research and application. In current research, two-dimensional carbon-based materials such as doped graphene and graphyne have been shown to have room temperature ferromagnetism, but due to insufficient spin coupling in the material and low spin polarization, their overall magnetic performance is poor. For example, in 2024, Yong Wang et al. (YongWang, Dingyi Yang, Wei Xu, Yongjie Xu, Yu Zhang, Zixuan Cheng, Yizhang Wu, XuetaoGan, Wei Zhong, Yan Liu, Genquan Han, Yue Hao. Room-temperature ferromagnetism and piezoelectricity in metal-free 2D semiconductor crystalline carbon nitride. Nano Research 2024, 17, 5670-5679) prepared pure crystalline carbon nitride by chemical vapor deposition, and its saturation magnetization at room temperature was only 0.01emu / g. In 2023, Lina Du et al. (Lina Du, Bo Gao, Song Xu, Qun Xu. Strong ferromagnetism of g-C3N4 achieved by atomic manipulation. Nature Communications 2023, 14, 2278) increased the saturation magnetization intensity of metal-free carbon nitride at room temperature to 0.043emu / g by introducing a boron bridge into graphite-like carbon nitride.In 2022, a Chinese invention patent with the announcement number CN115382505A disclosed a thiol-functionalized magnetic oxidized carbon nitride, whose magnetism can reach a high level when doped with iron, but it does not belong to metal-free carbon nitride, and its subsequent research and development is still limited by transition metal elements. Therefore, the preparation of two-dimensional carbon-based materials with high magnetism and room temperature ferromagnetism is a key challenge to promote the development of spin electronics, magnetic storage and topological quantum fields. Summary of the invention

[0003] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism and a preparation method and application thereof. By using urea as a raw material, calcining in the atmosphere, continuing to anneal in argon, and then undergoing edge quadruple heat treatment, a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism is obtained; the preparation method of the present invention has the characteristics of simple process, easy repeatability and low cost; the black carbon nitride prepared by the preparation method of the present invention has the characteristics of high purity, high magnetization intensity, high Curie temperature and strong room temperature ferromagnetism, and its performance can enable metal-free two-dimensional carbon-based materials to be practically applied in the fields of magnetism and quantum, and is a key material for the research and development of sp electron carbon-based room temperature ferromagnetism, which is conducive to the application and development of spin electronic devices, topological quantum devices and magnetic storage.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, using urea as a raw material, introducing a large number of nitrogen vacancies in the graphite-like phase structure of carbon nitride through calcination, annealing and quadruple heat treatment processes to obtain black carbon nitride, specifically comprising the following steps:

[0006] Step 1: calcining urea and then naturally cooling it to room temperature to obtain a light yellow powder; the purity of the urea is greater than or equal to 99%;

[0007] Step 2: Place the light yellow powder obtained in step 1 in a quartz boat and compact it flatly, then place it in a tube furnace. After all the air in the tube furnace is replaced with argon, anneal it to obtain a yellow powder. The mass of the light yellow powder used for annealing is not more than 5 mg / mm 2 ;

[0008] Step 3: Place the yellow powder obtained in step 2 on the edge of a quartz boat, and then place it in a tube furnace. After all the air in the tube furnace is replaced with argon, perform a quadruple heat treatment on the edge to obtain a black powder.

[0009] Step 4: Use anhydrous ethanol to centrifuge and wash the black powder obtained in step 3 for at least three times, and then perform low-temperature drying after washing to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism.

[0010] The calcination conditions in step 1 are: in an air atmosphere, heating to 530-570° C. at a rate of 1.5-3.5° C. / min and then maintaining the temperature for 2-4 hours.

[0011] The annealing conditions in step 2 are: under the protection of argon, heating to 660-700° C. at 20-30° C. / min and then keeping the temperature for 5-15 minutes.

[0012] The gas replacement process in step 2 lasts for at least 20 minutes, during which the flow rate of the argon gas is 200-300 cc / min; after the replacement process is completed, the flow rate of the argon gas is maintained at 20-50 cc / min.

[0013] The edge quadruple heat treatment process in step 3 is as follows:

[0014] The first heat treatment is: under the protection of argon, the temperature is raised to 720-760°C at 15-25°C / min, and then naturally cooled immediately until the temperature drops to room temperature;

[0015] The second heat treatment, the third heat treatment and the fourth heat treatment are all: under the protection of argon, the temperature is raised to 660-700°C at 15-25°C / min, and then natural cooling is immediately started. After the temperature drops to room temperature, this operation is repeated until the fourth heat treatment is completed.

[0016] The centrifugal washing in step 4 is ultrasonic dispersion and centrifugal separation, the ultrasonic oscillation time is ≥3 min, the centrifugal speed is 6000-8000 rpm, and the centrifugal time is ≥4 min; the low-temperature drying temperature is 40-60° C., and the drying process lasts at least 2 h.

[0017] The present invention also provides a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism obtained by the above preparation method.

[0018] The carbon nitride quantum material is an amorphous nanosheet with a two-dimensional layered structure, a single layer thickness of 4-15 nm, and a length or width of 1-10 μm.

[0019] The carbon nitride quantum material retains a graphite-like phase structure while having nitrogen vacancies in the carbon-nitrogen skeleton.

[0020] The present invention also provides an application of the two-dimensional black carbon nitride with room temperature ferromagnetism as described above in spin electronic devices, topological quantum devices or magnetic storage.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention obtains a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism by annealing and edge quadruple heat treatment of carbon nitride obtained by calcining urea in the atmosphere in an argon environment; the carbon nitride prepared by the preparation method of the present invention introduces more nitrogen vacancies into the carbon nitride skeleton while retaining the original graphite-like phase structure, thereby leading to the reconstruction of the CC bond and the p of the carbon atom. z The orbit is in an unsaturated state, providing black carbon nitride with an intrinsic magnetic moment derived from defects; at the same time, the localized spin state formed by the nitrogen vacancy couples with the adjacent carbon atom spins through indirect exchange, forming a long-range magnetic order, thereby exhibiting ferromagnetism at room temperature.

[0023] 2. The two-dimensional black carbon nitride prepared by the present invention has room-temperature ferromagnetism, and its Curie temperature exceeds 400K. When the temperature is 2K, the saturation magnetization is not less than 9.85emu / g, and the residual magnetization is not less than 1.58emu / g; when the temperature is 300K, the saturation magnetization is not less than 4.25emu / g, and the residual magnetization is not less than 0.77emu / g. The two-dimensional black carbon nitride prepared by the preparation method of the present invention can be used in a wide range of magnetic demand scenarios, especially in biomedicine, food and drug processing, environmental protection and other fields that require metal-free and non-toxicity, and can also be used in spin electronic devices, topological quantum devices and magnetic storage.

[0024] 3. The preparation method of the present invention has the characteristics of simple process, easy repeatability and low cost; the black carbon nitride prepared by the preparation method of the present invention has the characteristics of high purity, high magnetization intensity, high Curie temperature and strong room temperature ferromagnetism.

[0025] In summary, the present invention uses urea as a raw material, calcines in the atmosphere, continues to complete annealing in argon, and then undergoes edge quadruple heat treatment to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism; the preparation method of the present invention has the characteristics of simple process, easy repeatability and low cost; the black carbon nitride prepared by the preparation method of the present invention has the characteristics of high purity, high magnetization intensity, high Curie temperature and strong room temperature ferromagnetism, and its performance can enable metal-free two-dimensional carbon-based materials to be practically applied in the fields of magnetism and quantum, and is a key material for the research and development of sp electron carbon-based room temperature ferromagnetism, which is conducive to the application and development of spin electronic devices, topological quantum devices and magnetic storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the structure of the two-dimensional black carbon nitride provided by the present invention, wherein: Figure 1 a is a schematic diagram of the complete structure of graphite-like carbon nitride produced after calcination. Figure 1 b is a schematic diagram of the partial structure with a small amount of nitrogen vacancies after annealing. Figure 1 c and 1d are schematic diagrams of the partial structures that produce medium-sized nitrogen vacancies after heat treatment. Figure 1 e and 1f are schematic diagrams of the partial structures that produce a large number of nitrogen vacancies after heat treatment.

[0027] Figure 2 This is a physical optical photograph of the two-dimensional black carbon nitride provided by the present invention.

[0028] Figure 3 AFM height map of a single layer of two-dimensional black carbon nitride provided by the present invention.

[0029] Figure 4 The multilayer AFM image and MFM image of the two-dimensional black carbon nitride provided by the present invention, wherein: Figure 4 a is a multi-layer AFM height map, Figure 4 b is the corresponding MFM phase shift diagram.

[0030] Figure 5 The EDS spectrum of the two-dimensional black carbon nitride provided by the present invention, wherein: Figure 5 a is the morphology image under transmission electron microscope. Figure 5 b is the distribution diagram of carbon element in the corresponding area, Figure 5 c is the distribution map of nitrogen in the corresponding area.

[0031] Figure 6 The EELS spectrum of the two-dimensional black carbon nitride provided by the present invention, wherein: Figure 6 a is the morphology of the EELS characterization area. Figure 6 b is the mixed distribution diagram of carbon-nitrogen elements in the corresponding area, Figure 6 c is the distribution diagram of carbon element in the corresponding area, Figure 6 d is the distribution map of nitrogen in the corresponding area.

[0032] Figure 7 The XAS spectrum of the two-dimensional black carbon nitride provided by the present invention, wherein: Figure 7 a is the spectrum corresponding to nitrogen element, Figure 7 b is the spectrum corresponding to carbon element.

[0033] Figure 8 The XPS spectrum of the two-dimensional black carbon nitride provided by the present invention, wherein: Figure 8 a is the spectrum corresponding to nitrogen element, Figure 8 b is the spectrum corresponding to carbon element.

[0034] Fig. 9 This is the MT curve graph of the two-dimensional black carbon nitride provided by the present invention.

[0035] Fig.10 This is the MH curve of the two-dimensional black carbon nitride provided by the present invention at 2K.

[0036] Fig.11 This is the MH curve of the two-dimensional black carbon nitride provided by the present invention at 300K.

[0037] Fig.12 A photograph of the two-dimensional black carbon nitride provided by the present invention being attracted by an external magnetic field. DETAILED DESCRIPTION

[0038] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0039] like Figure 1-Figure 3 As shown, a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, the carbon nitride is an amorphous nanosheet with a two-dimensional layered structure, the single layer thickness is 4-15nm, the further thickness is 4.3-14.8nm, the length or width is 1-10μm; the carbon nitride retains a graphite-like phase structure while having nitrogen vacancies in the carbon-nitrogen skeleton; wherein, Figure 1 a is the graphite-like phase structure of the light yellow powder obtained in step 1; Figure 1 b is the structure of the yellow powder obtained in step 2. After annealing, its graphite-like phase structure has a small amount of lattice nitrogen vacancies in the carbon-nitrogen skeleton; Figure 1 cf is the structure of the black powder obtained by the stepwise heat treatment in step 3. With the increase of the number of heat treatments, more nitrogen vacancies gradually appear on the carbon-nitrogen skeleton in its graphite-like phase structure until the nitrogen vacancies are filled and the overall graphite-like phase carbon-nitrogen skeleton structure is maintained.

[0040] A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, using urea as a raw material, introducing a large number of nitrogen vacancies in the graphite-like phase structure of carbon nitride through calcination, annealing and quadruple heat treatment processes to obtain black carbon nitride, specifically comprising the following steps:

[0041] Step 1: calcining urea in a muffle furnace, and then naturally cooling to room temperature to obtain a light yellow powder; the calcination conditions are: heating to 530-570°C at 1.5-3.5°C / min in an air atmosphere and then keeping the temperature for 2-4 hours; the purity of the urea is greater than or equal to 99%;

[0042] Step 2: Place the light yellow powder obtained in step 1 in a quartz boat, spread it flat and compact it, and then put it into a tube furnace. After all the air in the tube furnace is replaced with argon, anneal it to obtain a yellow powder. The annealing conditions are: under the protection of argon, heat it to 660-700℃ at 20-30℃ / min and keep it warm for 5-15min. The mass of the light yellow powder used for annealing should not be greater than 5mg / mm 2 The gas replacement process lasts at least 20 minutes, during which the flow rate of argon gas is 200-300cc / min; after the replacement process, the flow rate of argon gas should be maintained at 20-50cc / min;

[0043] Step 3: placing the yellow powder obtained in step 2 on the edge of a quartz boat, and then placing it in a tube furnace, and after all the air in the tube furnace is replaced with argon, performing a quadruple heat treatment on the edge to obtain a black powder; the quadruple heat treatment process of the edge is: firstly performing a first heat treatment, that is, under the protection of argon, heating to 720-760°C at 15-25°C / min, and immediately starting natural cooling until the temperature drops to room temperature; then performing a second heat treatment, a third heat treatment, and a fourth heat treatment in sequence, the heat treatments are all: under the protection of argon, heating to 660-700°C at 15-25°C / min, and immediately starting natural cooling, and after the temperature drops to room temperature, repeating this operation until the fourth heat treatment is completed;

[0044] Step 4: The black powder obtained in step 3 is centrifugally washed at least three times with anhydrous ethanol, and then subjected to low-temperature drying to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, such as Figure 2 As shown; the centrifugal washing is ultrasonic dispersion and centrifugal separation, the ultrasonic oscillation time is ≥3min, the centrifugal speed is 6000-8000rpm, and the centrifugal time is ≥4min; the temperature required for low-temperature drying is 40-60°C, and the drying process lasts at least 2h.

[0045] Example 1

[0046] A two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, wherein the two-dimensional black carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a single layer thickness of 4-5.3 nm and a length or width of 1-4.2 μm.

[0047] A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, specifically comprising the following steps:

[0048] Step 1: Weigh 2 g of urea and spread it evenly on the bottom of a clean crucible with a lid, then place it in a muffle furnace, heat it to 550°C at 2.5°C / min in an air atmosphere, and keep it warm for 3 hours. After the end of the heat preservation, naturally cool it to room temperature to obtain a light yellow powder;

[0049] Step 2: 1 g of light yellow powder was evenly spread in a quartz boat with a bottom of 20 mm × 20 mm and compacted, and then placed in a tube furnace, argon gas was introduced, and the gas flow rate was adjusted to 200 cc / min, and maintained for 20 min, and then the gas flow rate was adjusted to 20 cc / min, and the temperature was raised to 680 ° C at 20 ° C / min, and maintained for 10 min. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a yellow powder;

[0050] Step 3: The yellow powder obtained in step 2 is concentrated at the edge of the quartz boat, placed in a tube furnace, argon gas is introduced, the gas flow rate is adjusted to 200cc / min, and maintained for 20min, and then the gas flow rate is adjusted to 20cc / min, and the first heat treatment is started: the temperature is increased to 750°C at 20°C / min, and then natural cooling is immediately started until the temperature drops to room temperature, and the second heat treatment is started: the temperature is increased to 660°C at 20°C / min, and then natural cooling is immediately started until the temperature drops to room temperature; the third heat treatment and the fourth heat treatment are sequentially performed to obtain a black powder; the process parameters of the third heat treatment and the fourth heat treatment are consistent with those of the second heat treatment;

[0051] Step 4: Disperse the black powder obtained in step 3 in anhydrous ethanol, ultrasonically oscillate for 5 minutes, and then centrifuge at 6000 rpm for 8 minutes, remove the solution, retain the precipitate, add deionized water again, repeat the oscillation and centrifugation, repeat five times, and then place the final precipitate in an oven at 40°C and bake for 6 hours to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism.

[0052] Example 2

[0053] A two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, wherein the two-dimensional black carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a single layer thickness of 5.3-7.6 nm and a length or width of 3-5.5 μm.

[0054] A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, specifically comprising the following steps:

[0055] Step 1: Weigh 2 g of urea and spread it evenly on the bottom of a clean crucible with a lid, then place it in a muffle furnace, heat it to 530 ° C at 1.5 ° C / min, keep it warm for 2 hours, and naturally cool it to room temperature after the end of the insulation to obtain a light yellow powder;

[0056] Step 2: 2 g of light yellow powder was evenly spread in a quartz boat with a bottom of 20 mm × 20 mm and compacted, and then placed in a tube furnace, argon gas was introduced, and the gas flow rate was adjusted to 255 cc / min, and maintained for 25 min, and then the gas flow rate was adjusted to 27 cc / min, and the temperature was raised to 700 ° C at 22 ° C / min, and maintained for 5 min. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a yellow powder;

[0057] Step 3: The yellow powder obtained in step 2 is concentrated at the edge of the quartz boat, placed in a tube furnace, argon gas is introduced, the gas flow rate is adjusted to 255cc / min, and maintained for 25min, then the gas flow rate is adjusted to 27cc / min, and the first heat treatment is started: the temperature is increased to 720°C at 15°C / min, and then natural cooling is immediately started until the temperature drops to room temperature, and the second heat treatment is started: the temperature is increased to 670°C at 15°C / min, and then natural cooling is immediately started until the temperature drops to room temperature; the third heat treatment and the fourth heat treatment are sequentially performed to obtain a black powder; the process parameters of the third heat treatment and the fourth heat treatment are consistent with those of the second heat treatment;

[0058] Step 4: Disperse the black powder obtained in step 3 in anhydrous ethanol, ultrasonically oscillate for 3 minutes, and then centrifuge at 6800 rpm for 7 minutes, remove the solution, retain the precipitate, add deionized water again, repeat the oscillation and centrifugation, repeat four times, and then place the final precipitate in an oven at 50°C and bake for 5 hours to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism.

[0059] Example 3

[0060] A two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, wherein the two-dimensional black carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a single layer thickness of 8.1-11 nm and a length or width of 4.5-6.2 μm.

[0061] A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, specifically comprising the following steps:

[0062] Step 1: Weigh 2 g of urea and spread it evenly on the bottom of a clean crucible with a lid, then place it in a muffle furnace, heat it to 540°C at 2°C / min, keep it warm for 4 hours, and naturally cool it to room temperature after the end of the insulation to obtain a light yellow powder;

[0063] Step 2: 1 g of light yellow powder was evenly spread in a quartz boat with a bottom of 20 mm × 50 mm and compacted, and then placed in a tube furnace, and argon gas was introduced, and the gas flow rate was adjusted to 240 cc / min, and maintained for 30 min, and then the gas flow rate was adjusted to 36 cc / min, and the temperature was raised to 690 ° C at 24 ° C / min, and maintained for 7 min. After the end of the heat preservation, it was naturally cooled to room temperature to obtain a yellow powder;

[0064] Step 3: The yellow powder obtained in step 2 is concentrated at the edge of the quartz boat, placed in a tube furnace, argon gas is introduced, the gas flow rate is adjusted to 240cc / min, and maintained for 30 minutes, and then the gas flow rate is adjusted to 36cc / min, and the first heat treatment is started: the temperature is increased to 730°C at 18°C / min, and then natural cooling is immediately started until the temperature drops to room temperature, and the second heat treatment is started: the temperature is increased to 680°C at 18°C / min, and then natural cooling is immediately started until the temperature drops to room temperature; the third heat treatment and the fourth heat treatment are sequentially performed to obtain a black powder; the process parameters of the third heat treatment and the fourth heat treatment are consistent with those of the second heat treatment;

[0065] Step 4: Disperse the black powder obtained in step 3 in anhydrous ethanol, ultrasonically oscillate for 10 minutes, and then centrifuge at 7000 rpm for 6 minutes, remove the solution, retain the precipitate, add deionized water again, repeat the oscillation and centrifugation, repeat three times, and then place the final precipitate in an oven at 60°C and bake for 2 hours to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism.

[0066] Example 4

[0067] A two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, wherein the two-dimensional black carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a single layer thickness of 10.7-13.4 nm and a length or width of 6.4-7.2 μm.

[0068] A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, specifically comprising the following steps:

[0069] Step 1: Weigh 2 g of urea and spread it evenly on the bottom of a clean crucible with a lid, then place it in a muffle furnace, heat it to 570°C at 3°C / min, keep it warm for 2.5 hours, and naturally cool it to room temperature after the end of the insulation to obtain a light yellow powder;

[0070] Step 2: 2 g of light yellow powder was evenly spread in a quartz boat with a bottom of 20 mm × 50 mm and compacted, and then placed in a tube furnace, argon gas was introduced, and the gas flow rate was adjusted to 270 cc / min, and maintained for 23 min, and then the gas flow rate was adjusted to 40 cc / min, and the temperature was raised to 670 ° C at 25 ° C / min, and maintained for 12 min. After the insulation was completed, it was naturally cooled to room temperature to obtain a yellow powder;

[0071] Step 3: The yellow powder obtained in step 2 is concentrated at the edge of the quartz boat, placed in a tube furnace, argon gas is introduced, the gas flow rate is adjusted to 270cc / min, and maintained for 23min, then the gas flow rate is adjusted to 40cc / min, and the first heat treatment is started: the temperature is increased to 740°C at 25°C / min, and then natural cooling is immediately started until the temperature drops to room temperature, and the second heat treatment is started: the temperature is increased to 690°C at 25°C / min, and then natural cooling is immediately started until the temperature drops to room temperature; the third heat treatment and the fourth heat treatment are sequentially performed to obtain a black powder; the process parameters of the third heat treatment and the fourth heat treatment are consistent with those of the second heat treatment;

[0072] Step 4: Disperse the black powder obtained in step 3 in anhydrous ethanol, ultrasonically oscillate for 6 minutes, and then centrifuge at 8000 rpm for 4 minutes, remove the solution, retain the precipitate, add deionized water again, repeat the oscillation and centrifugation, repeat three times, and then place the final precipitate in an oven at 55°C and bake for 3 hours to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism.

[0073] Example 5

[0074] A two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, wherein the two-dimensional black carbon nitride is in the form of a two-dimensional layered amorphous nanosheet with a single layer thickness of 13.5-15 nm and a length or width of 8.8-10 μm.

[0075] A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, specifically comprising the following steps:

[0076] Step 1: Weigh 2 g of urea and spread it evenly on the bottom of a clean crucible with a lid, then place it in a muffle furnace, heat it to 560°C at 3.5°C / min, keep it warm for 3.3 hours, and naturally cool it to room temperature after the end of the heat preservation to obtain a light yellow powder;

[0077] Step 2: 1.5 g of light yellow powder was evenly spread in a quartz boat with a bottom of 20 mm × 20 mm and compacted, and then placed in a tube furnace, argon gas was introduced, and the gas flow rate was adjusted to 300 cc / min, and maintained for 35 min, and then the gas flow rate was adjusted to 50 cc / min, and the temperature was raised to 660°C at 30°C / min, and maintained for 15 min. After the insulation was completed, it was naturally cooled to room temperature to obtain a yellow powder;

[0078] Step 3: The yellow powder obtained in step 2 is concentrated at the edge of the quartz boat, placed in a tube furnace, argon gas is introduced, the gas flow rate is adjusted to 300cc / min, and maintained for 35 minutes, and then the gas flow rate is adjusted to 50cc / min, and the first heat treatment is started: the temperature is increased to 760°C at 25°C / min, and then natural cooling is immediately started until the temperature drops to room temperature, and the second heat treatment is started: the temperature is increased to 700°C at 25°C / min, and then natural cooling is immediately started until the temperature drops to room temperature; the third heat treatment and the fourth heat treatment are sequentially performed to obtain a black powder; the process parameters of the third heat treatment and the fourth heat treatment are consistent with those of the second heat treatment;

[0079] Step 4: Disperse the black powder obtained in step 3 in anhydrous ethanol, ultrasonically oscillate for 5 minutes, and then centrifuge at 7500 rpm for 5 minutes, remove the solution, retain the precipitate, add deionized water again, repeat the oscillation and centrifugation, repeat three times, and then place the final precipitate in an oven at 50°C and bake for 4 hours to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism.

[0080] The two-dimensional black carbon nitride with room temperature ferromagnetism prepared in the above embodiments can be used in spin electronic devices, topological quantum devices and magnetic storage.

[0081] like Figure 3 As shown, it can be seen from the atomic force microscope image that the carbon nitride prepared by the present invention is a single-layer amorphous nanosheet with a thickness of 4.3 nm, a length of about 4.9 μm, and a width of about 4.0 μm, indicating that the carbon nitride prepared by the present invention has a two-dimensional property.

[0082] like Figure 4 As shown in b, it can be seen from the magnetic force microscope that the carbon nitride prepared by the present invention shows obvious room temperature ferromagnetic signals. Figure 4 a It can be seen that the carbon nitride has an obvious multilayer structure, and the thickness of each layer is 4-5.1 nm, indicating that the carbon nitride prepared by the present invention has an obvious two-dimensional layered structure and is ferromagnetic at room temperature.

[0083] like Figure 5 As shown, it can be seen from the transmission electron microscope image that carbon and nitrogen are evenly distributed in the carbon nitride, indicating that the two-dimensional black carbon nitride prepared by the present invention is an amorphous nanosheet.

[0084] like Figure 6 As shown, it can be seen from the transmission electron microscope image that the carbon and nitrogen elements of the two-dimensional black carbon nitride prepared by the present invention are still evenly distributed in a small scale range, but the nitrogen content is significantly lower than the carbon content, indicating that a large number of nitrogen vacancies are formed in the black carbon nitride.

[0085] like Figure 7 and Figure 8 As shown, the two-dimensional black carbon nitride prepared by the present invention contains chemical bonds in different states, that is, NC3, CN=C, N=CN, NCN and CN bonds exist simultaneously, revealing that the graphite-like phase structure is distorted and a large number of nitrogen vacancies are introduced.

[0086] like Fig. 9 As shown, the MT curves of the two-dimensional black carbon nitride prepared by the present invention under zero field cooling (ZFC) and field cooling (FC) under an external magnetic field of 1000Oe show that the Curie temperature exceeds 400K, indicating that the two-dimensional black carbon nitride is a room temperature ferromagnetic material.

[0087] like Fig.10 As shown, the saturation magnetization intensity M of the two-dimensional black carbon nitride prepared by the present invention at 2K S is 9.85emu / g, and the residual magnetization intensity M r is 1.58emu / g, and the coercive field H C is 502Oe; Fig.11 As shown, the saturation magnetization intensity M of the two-dimensional black carbon nitride prepared by the present invention at 300K S is 4.25emu / g, and the residual magnetization intensity M r is 0.77emu / g, and the coercive field H C It is 203Oe; compared with the existing two-dimensional carbon-based materials, it is shown that the two-dimensional black carbon nitride prepared by the present invention has a high saturation magnetization intensity and has magnetic properties that can be used in practical applications at room temperature.

[0088] like Fig.12 As shown, the two-dimensional black carbon nitride prepared by the present invention can be attracted by the external magnetic field applied by a permanent magnet in an atmospheric environment at room temperature, indicating that the two-dimensional black carbon nitride prepared by the preparation method of the present invention has strong room-temperature ferromagnetism.

Claims

1. A method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism, characterized in that: Urea is used as a raw material, and a large number of nitrogen vacancies are introduced into the graphite-like phase structure of carbon nitride through calcination, annealing and quadruple heat treatment processes to obtain black carbon nitride, which specifically includes the following steps: Step 1: calcining urea and then naturally cooling it to room temperature to obtain a light yellow powder; the purity of the urea is greater than or equal to 99%; Step 2: Place the light yellow powder obtained in step 1 in a quartz boat and compact it flatly, then place it in a tube furnace. After all the air in the tube furnace is replaced with argon, anneal it to obtain a yellow powder. The mass of the light yellow powder used for annealing is not more than 5 mg / mm 2 ; Step 3: Place the yellow powder obtained in step 2 on the edge of a quartz boat, and then place it in a tube furnace. After all the air in the tube furnace is replaced with argon, perform a quadruple heat treatment on the edge to obtain a black powder. Step 4: Use anhydrous ethanol to centrifuge and wash the black powder obtained in step 3 for at least three times, and then perform low-temperature drying after washing to obtain a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism.

2. The method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism according to claim 1, characterized in that: The calcination conditions in step 1 are: in an air atmosphere, heating to 530-570° C. at a rate of 1.5-3.5° C. / min and then maintaining the temperature for 2-4 hours.

3. The method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism according to claim 1, characterized in that: The annealing conditions in step 2 are: under the protection of argon, heating to 660-700° C. at 20-30° C. / min and then keeping the temperature for 5-15 minutes.

4. The method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism according to claim 1 or 3, characterized in that: The gas replacement process in step 2 lasts for at least 20 minutes, during which the flow rate of the argon gas is 200-300 cc / min; after the replacement process is completed, the flow rate of the argon gas is maintained at 20-50 cc / min.

5. The method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism according to claim 1, characterized in that: The edge quadruple heat treatment process in step 3 is as follows: The first heat treatment is: under the protection of argon, the temperature is raised to 720-760°C at 15-25°C / min, and then naturally cooled immediately until the temperature drops to room temperature; The second heat treatment, the third heat treatment and the fourth heat treatment are all: under the protection of argon, the temperature is raised to 660-700°C at 15-25°C / min, and then natural cooling is immediately started. After the temperature drops to room temperature, this operation is repeated until the fourth heat treatment is completed.

6. The method for preparing a two-dimensional black carbon nitride quantum material with room temperature ferromagnetism according to claim 1, characterized in that: The centrifugal washing in step 4 is ultrasonic dispersion and centrifugal separation, the ultrasonic oscillation time is ≥3 min, the centrifugal speed is 6000-8000 rpm, and the centrifugal time is ≥4 min; the low-temperature drying temperature is 40-60° C., and the drying process lasts at least 2 h.

7. A two-dimensional black carbon nitride quantum material with room temperature ferromagnetism obtained by the preparation method according to any one of claims 1 to 6.

8. The two-dimensional black carbon nitride quantum material with room temperature ferromagnetism according to claim 7, characterized in that: The carbon nitride quantum material is an amorphous nanosheet with a two-dimensional layered structure, a single layer thickness of 4-15 nm, and a length or width of 1-10 μm.

9. The two-dimensional black carbon nitride quantum material with room temperature ferromagnetism according to claim 7, characterized in that: The carbon nitride quantum material retains a graphite-like phase structure while having nitrogen vacancies in the carbon-nitrogen skeleton.

10. An application of the two-dimensional black carbon nitride quantum material with room temperature ferromagnetism as claimed in any one of claims 8 or 9 in spin electronic devices, topological quantum devices or magnetic storage.

Citation Information

Patent Citations

  • Preparation method and application of sulfydryl-functionalized magnetic nitric carbonitride nano composite material

    CN115382505A

  • Preparation method of fluffy carbon nitride nano catalytic material with high catalytic activity

    CN104368383A

  • Method for preparing carbon nitride film

    CN105331949A

  • Preparation method of amorphous graphite-state carbon nitride with characteristic of large-amplitude light absorption edge red shift

    CN106268897A

  • Green carbon nitride, preparation method and applications thereof

    CN110683523A